Analysis of Trade and Environmental Policy Options on the Basis of a National Agricultural Sector Model with Multifunctional Outputs - Gerald Weber (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
SummaryStudies on liberalisation normally do not take into account the external benefits and costs of agriculture. Empirical studies on the valuation of externalities should be integrated into quantitative modelling. MULTSIM is a national supply model of agriculture. Besides commodity output the model depicts also external benefit linked to landscape preservation and external environmental costs of agriculture. Internalisation scenarios are defined showing that the reduction of commodity-linked support and the introduction of land subsidies and intermediate input taxes have differentiated impacts on the farm types' competitiveness. A comprehensive policy approach to multifunctional agriculture requires market feedbacks to be taken into account. Internalising externalities may lead to a strong reduction of commodity output quantities. This gives rise to expectations that commodity prices would increase, which in turn would dampen the production impacts. As a consequence MULTSIM should be regarded as a bridge tool that may be linked to microeconomic based multi market models and agricultural trade models. A further strain of model development is an improved consideration of multiple policy objectives.
Keywords: 330; Landwirtschaft; Umweltbelastung; Internalisierung externer Effekte; Politikberatung; Agrarökonomik